Idiosyncatic recognition of Zn2+ and CN− using pyrazolyl-hydroxy-coumarin scaffold and live cell imaging: depiction of luminescent Zn(ii)-metallocryptand. Issue 8 (4th February 2022) - Paul, Sukanya; Maity, Suvendu; Halder, Satyajit; Dutta, Basudeb; Jana, Srikanta; Jana, Kuladip; Sinha, Chittaranjan
Abstract : Pyrazolyl coumarin scaffold has been used for the selective detection of Zn 2+ and CN − and has been successfully applied for intracellular imaging of Zn 2+ and CN − in MDA-MB 231 cells. The probe isolates a unique emissive hexanuclear Zn-metallocryptand. Abstract : Multi-responsive and selective sensor design is one of the stimulating research areas in the sensors field. We have designed a pyrazolyl-hydroxy-coumarin scaffold, 7-hydroxy-4-methyl-8-(((5-phenyl-1 H -pyrazol-3-yl)imino)methyl)-2 H -chromen-2-one (H2 L) and characterized it by spectroscopic techniques ( 1 H NMR, 13 C NMR, ESI-MS, IR). The single crystal X-ray diffraction measurement confirms the molecular structure of the probe. It shows the selective sensing of Zn 2+ in the presence of sixteen other cations with 'Turn On' approach through the enhancement of green florescence (( λ em = 499 nm; λ ex = 390 nm) in CH3 CN/H2 O (99 : 1, v/v; HEPES buffer, pH 7.5) medium with the limit of detection (LOD) of 34.76 nM. The structural depiction of the isolated Zn 2+ complex reveals cage like metallocryptand cyclic hexamer, [Zn6 L6 ] with 30.9% void of cavity along the crystallographic c axis of approximate dimension of 7.502 × 7.050 × 7.068 Å 3 . The diffusion NMR study reveals only one type of complex in the solution, having 1 : 1 composition, i.e., Zn 2+  : H2 L, which affirms the isolated form of the complex. On the other hand, the receptor, H2 L, recognizes the very noxious anion CN − out of sixteen anions. The product identification using spectroscopic techniques supports the nucleophilic addition of CN − across the exocyclic imine (CN) bond, which shows blue emission (( λ em = 447 nm; λ ex = 390 nm), and the LOD was 19.91 nM. The composition of [H2 L−Zn 2+ ] and [H2 L−CN − ] was established by 1 H NMR titration, Job's method, ESI-MS, and FTIR spectra. The efficacy of the probe was further studied using MTT assay in MDA-MB 231 and WI-38 cell line as well as for the intracellular imaging of Zn 2+ and CN − using a fluorescence microscope. Flow Cytometry was further performed for the quantitative analysis of Zn 2+ distribution in MDA-MB 231 cells.